2021
DOI: 10.3389/fcvm.2021.657817
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index-C: An Updated and Simple Risk-Stratifying Tool in ST-Segment Elevation Myocardial Infarction

Abstract: Background: Shock index (heart rate/systolic blood pressure, SI) is a simple scale with prognostic value in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). The present study introduces an updated version of SI that includes renal function.Methods: A total of 1,851 consecutive patients with STEMI undergoing PCI were retrospectively included at Cardiac Care Unit in Guangdong Provincial People's Hospital and divided into two groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Another pertinent finding exhibited on multivariate regression analysis was that SI-C retained the predictive power as an independent and significant risk stratification tool for CIN with p-value of <0.001 in contrast to Mehran risk score which lost its statistical significance (p=0.796) to demonstrate the correlation with CIN as an independent factor. Our findings contradict the observation made by Ran P et al 15 , who introduced SI-C as a novel risk score and explored its discriminative ability against MRS to identify the risk of CIN. According to their study, SIC didn't perform well in comparison with MRS for predicting CIN (AUC: 0.707 vs. 0.749, p = 0.029).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Another pertinent finding exhibited on multivariate regression analysis was that SI-C retained the predictive power as an independent and significant risk stratification tool for CIN with p-value of <0.001 in contrast to Mehran risk score which lost its statistical significance (p=0.796) to demonstrate the correlation with CIN as an independent factor. Our findings contradict the observation made by Ran P et al 15 , who introduced SI-C as a novel risk score and explored its discriminative ability against MRS to identify the risk of CIN. According to their study, SIC didn't perform well in comparison with MRS for predicting CIN (AUC: 0.707 vs. 0.749, p = 0.029).…”
Section: Discussioncontrasting
confidence: 99%
“…23 CHA2DS2-VASc score of > 4 has also emerged as a strong contender for the identification of increased risk of CIN in STEMI patients with AUC reported as 0.88 (CI 0.82-0.94). 14 Last but not least, the AUC of SI 15 for estimation of CIN in post primary PCI patients has been documented as 0.577 (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Shangguan et al revealed that the MSI has a better predictive value for seven-day mortality and MACEs in STEMI when compared with SI [ 15 ]. Recently, Ran et al established a new score, the shock index-C (SIC; (SI × 100) estimated creatinine clearance rate (CCr)), and found that SIC had a better predictive value than the SI and even better than traditional risk scales, such as TIMI risk scales [ 16 ]. However, there is a lack of evidence comparing SIC, the SI, MSI, and delta-SI in predicting the short-term outcomes of STEMI.…”
Section: Introductionmentioning
confidence: 99%